Torrefaction process : the effect of temperature and residence time to the production of torrefied rubberwood - Muhammad Faisal, Baderolhissam (2014)
This thesis presents the study on the effect of temperature and residence time towards the torrefied rubberwood fibre characteristics. In order to produce the biomass product from the rubberwood fibre (RWF), torrefaction process of the sample remove the moisture and oxygen content inside by applying the process with the temperature in range between 200-300 °C (Stelt et.tal., 2008). The torrefaction process might change the morphology structure, decomposition pattern, wavelength spectrum and most importantly its energy value. This research is important in studying the effect of the temperature and residence time during the torrefaction process on the characteristics of the rubberwood fibre. In this research, the temperature applied for the torrefaction was 180 °C, 250 °C and 320 °C to investigate the effect of temperature towards the product. The heating rate use was 10°C/min and the nitrogen gas was flush throughout the tubular glass reactor for 15min before the process. Holding time in the process also being manipulated at each temperature used by 10, 20 and 30min. The characteristic data of rubberwood fibre(RWF) after torrefaction was collected and compared by using fourier transforms infrared spectroscopy (FTIR) to define wavelength, scanning electron microscope (SEM) to get the surface morphology of the product, thermal gravimetric analysis (TGA) to recognize materials characterization through analysis of characteristic decomposition patterns, and lastly the most important is bomb calorimeter to measure the energy value for the combustion. SEM structure at 3K X magnificent, the structure of the torrefied product at 320°C shows significant difference compared to the others. In contrast, the structure of the other two torrefieds product at different temperature and constant residence time shows no major change. The result then compared with FTIR analysis at which it shows loss of functional group represent the RFW component especially hemicellulose for torrefied RWF at 320°C. Based on the energy value of the product, it can be concluded that the higher the temperature of torrefaction, the higher the energy value of the product. The graph of percentage of weight versus temperature from TGA concludes that the torrefied RWF at higher temperature takes longer time to decompose